How the combination of PhIO and I2 provides a species responsible for conducting organic reactions through radical mechanisms. Issue 40 (2nd October 2020) - Farshadfar, Kaveh; Gouranourimi, Ali; Ariafard, Alireza
Abstract : This contribution provides an answer to the long-standing question of how organic radicals are produced by the PhIO/I2 system and how the ensuing radicals are oxidized by the same system to yield the organic products. Abstract : A combination of iodosobenzene (PhIO) and molecular iodine (I2 ) is well-documented to produce a key species capable of conducting various organic reactions through radical mechanisms. This key species is identified here by density functional theory (DFT) calculations to be the hypoiodite radical (IO˙). The calculations show that two equivalents of IO˙ are generated when I2 reacts with two equivalents of PhIO. One of the ensuing IO˙ species acts as a hydrogen abstractor and thus forms an organic radical and the other one is involved in oxidation of the resultant organic radical to afford the final product.